KETERAMPILAN BERPIKIR KREATIF SISWA MENGGUNAKAN MODEL PBL (Problem Based Learning) DENGAN PENDEKATAN STEM PADA MATERI VEKTOR DI KELAS X MIPA 4 SMA NEGERI 2 JEMBER - Mardiyah Sari Dewi; Albertus Djoko Lesmono; Hadiyanto Hadiyanto; Arif Harimukti (Universitas Jember, 2020)
This study discusses how students think about vector material through PBL (Problem Based Learning) models using STEM (Science, Technology, Engineering, and Mathematics). The method used in this study uses qualitative descriptive research. The subjects of this study were students of grade X MIPA 4 SMA Negeri 2 Jember with a total of 35 students. The instruments of collecting data in this study consisted of student worksheets and questionnaires to measure students' creative thinking skills. Student worksheets are provided using STEM (Science, Technology, Engineering, and Mathematics) which have been adapted to the 2013 curriculum that directs students to be actively involved in learning activities. fluency, flexibility, elaboration and originality which contains 6 indicators. The results of the questionnaire data were analyzed based on its indicators, namely for the first indicator getting a percentage of creative thinking skills by 74%, the second indicator by 78%, the third indicator by 74%, the percentage indicator by 69%, the percentage indicator by 74%, and for the sixth indicator by 70% . The number of students who reached the criteria was quite creative there were 33 students with a percentage of 94%. Based on the results of data analysis obtained, students think a high percentage. The PBL (Problem Based Learning) model using STEM (Science, Technology, Engineering, and Mathematics) on vector material has good implications and supports an effective and enjoyable learning process for students.